C Terminus of Nucleotide Binding Domain 1 Contains Critical Features for Cystic Fibrosis Transmembrane Conductance Regulator Trafficking and Activation - Billet, Arnaud (American Society for Biochemistry and Molecular Biology, 2010)
The cystic fibrosis transmembrane conductance regulator (CFTR) is a Cl(−) channel physiologically important in fluid-transporting epithelia and pathologically relevant in several human diseases. Here, we show that mutations in the C terminus of the first nucleotide binding domain comprising the latest β strands (β(c)5 and β(c)6) influence the trafficking, channel activity, and pharmacology of CFTR. We mutated CFTR amino acids located in the β(c)5-β(c)6 hairpin, within the β(c)5 strand (H620Q), within the β-turn linking the two β strands (E621G, G622D), as well as within (S623A, S624A) and at the extremity (G628R) of the β(c)6 strand. Functional analysis reveals that the current density was largely reduced for G622D and G628R channels compared with wt CFTR, similar for E621G and S624A, but increased for H620Q and S623A. For G622D and G628R, the abnormal activity is likely due to a defective maturation process, as assessed by the augmented activity and mature C-band observed in the presence of the trafficking corrector miglustat. In addition, in presence of the CFTR activator benzo[c]quinolizinium, the CFTR current density compared with that of wt CFTR was abolished for G622D and G628R channels, but similar for H620Q, S623A, and S624A or slightly increased for E621G. Finally, G622D and G628R were activated by the CFTR agonists genistein, RP-107, and isobutylmethylxanthine. Our results identify the C terminus of the CFTR first nucleotide binding domain as an important molecular site for the trafficking of CFTR protein, for the control of CFTR channel gating, and for the pharmacological effect of a dual activity agent.